Biomimetic Materials for Regenerative Medicine: Design and Applications - Jain Toshit; Sujani Singavarapu; Singh Navdeep; Al-Alawachi Sharif Fadhil Abood; V Asha; Meheta Ankit (E3S Web of Conferences, 2024)
Bio mimetic materials have shown great potential for tissue engineering and regenerative medicine as they can mimic the natural extracellular matrix (ECM) of tissues and organs. The ECM is a complex network of proteins, glycosaminoglycans, and other bio molecules that provide structural support to cells and regulate their behaviour. Bio mimetic materials can be designed to replicate the biochemical and biophysical properties of the ECM, creating an environment that promotes cell adhesion, proliferation, differentiation, and tissue regeneration. There are different classes of bio mimetic materials, including natural and synthetic polymers, as well as inorganic materials such as Hydroxyapatite and ceramics. Polymers made from nature that assist with with cell growth and differentiation, like collagen, which is fibrin, and hyaluronic acid, for instance, have been utilised extensively in tissue engineering. Both the physical and chemical characteristics of synthetic polymers, which include polyethylene glycol, also known as PEG, and poly lactic acid (PLA), can be modified to satisfy the needs of different tissues. Inorganic materials such as hydroxyapatite and ceramics can mimic the mineralized ECM of bone and tooth tissues, providing a scaffold for cell attachment and mineral deposition. Recent advances in the field of bio mimetic materials include the use of nanotechnology and 3D printing to create complex structures with precise control over their size, shape, and mechanical properties. Nanoparticles and nano fibers can be incorporated into bio mimetic materials to enhance their mechanical strength, surface area, and bioactivity. 3D printing can be used to create customized scaffolds that match the shape of the target tissue, allowing for more effective tissue regeneration.